THE EFFECT OF STUDENT SELF-EFFICACY AND ACHIEVEMENT MOTIVATION ON LEARNING INDEPENDENCE IN COMPUTER ACCOUNTING COURSE - Handika Asep Kurniawan (Sean Institute, 2022)
This study aims to determine the effect of Self-Efficacy and Achievement Motivation on Learning Independence in Computer Accounting Courses. The subjects of this study were fourth semester students of the accounting study program. This type of research is ex-post facto research and the instrument used is a questionnaire. Data analysis techniques using quantitative descriptive data analysis. The validity of the data is obtained through validity and reliability. The results showed that: (1) There is a positive and significant influence between Self-Efficacy on Learning Independence in Computer Accounting Courses of 33.7% as seen from the value of tcount = 3.770 (> ttable = 2.042), at a significance of 5%, (2) There is a positive and significant influence between Achievement Motivation and Learning Independence in Computer Accounting Courses of 27.1% as seen from the value of tcount = 3.224 (> ttable = 2.042), at a significance of 5%, and (3) There is a positive influence and the significant difference between Self-Efficacy and Achievement Motivation together Learning Independence in Computer Accounting Course is 37.2% as seen from the value of Fcount = 7.983 (> Ftable = 3.35) at 5% significance.